NILAI PENDIDIKAN KARAKTER DAN KONFLIK BATIN TOKOH UTAMA PADA NOVEL SINAR KARANGAN AGUK IRAWAN MIZAN - Risma Martalena Tarigan (Universitas Negeri Medan, 2019)
Abstract The purpose of this study is to (1) Analyze the value of character education in the novel Sinar by Aguk Irawan Mizan's novel, (2) Analyze the inner conflict of the main characters in the novel Sinar by Aguk Irawan Mizan's novel and (3) Arrange the results of the study as literary reading material in high school. This research is a qualitative research with descriptive method and researchers as instruments. The value of character education is analyzed with the provisions of the Ministry of National Education that is limited to religious values, the value of hard work, the value of independence, the value of responsibility and the value of social care. Inner conflict was analyzed by Sigmund Freud's theory. Data were collected through the note-taking technique and then analyzed using the Miles and Huberman models. Its usefulness as reading material is known through interviews with three Indonesian language teachers and questionnaires for 32 students in SMA 4 Binjai. Based on the research, 33 values of character education were obtained which included five religious values, four values of hard work, twelve values of independence, eight values of responsibility and four values of social care. In addition, there are fifteen inner conflicts of the main characters in the novel. Based on the results of the interview it was concluded that the reading material in the form of enrichment books based on this study was appropriate to be used as a companion learning book and in accordance with the characteristics of high school students. The results of the questionnaire showed students' responses to reading material by 82.2% with very good criteria. Keywords: Value of Character Education, Inner Conflict, Novels, Reading Materials.